[18F]FE-PE2I DAT correlates with Parkinson’s disease duration, stage, and rigidity/bradykinesia scores: a PET radioligand validation study - Vera S. Kerstens; Patrik Fazio; Mathias Sundgren; Christer Halldin; Per Svenningsson; Andrea Varrone (EJNMMI Research, 2023)
Abstract Background Correlations between dopamine transporter (DAT) availability and Parkinson’s disease (PD) motor symptoms vary depending on the imaging modality, choice of regions of interest and clinical measures. We aimed to validate the PET radioligand [18F]FE-PE2I as a clinical biomarker in PD, hypothesizing negative correlations between DAT availability in specified nigrostriatal regions with symptom duration, disease stage and motor symptom scores. Methods We included 41 PD patients (age 45–79 years; H&Y stage < 3) and 37 healthy control subjects in a cross-sectional study with dynamic [18F]FE-PE2I PET. Binding potential (BPND) was estimated in the caudate nucleus, putamen, ventral striatum, sensorimotor striatum, and substantia nigra using the cerebellum as reference region. Results We found negative correlations (p < 0.02) between symptom duration and BPND in the putamen and sensorimotor striatum (r s = − .42; r s = − .51), and between H&Y stage and BPND in caudate nucleus, putamen, sensorimotor striatum, and substantia nigra (r s between − .40 and − .54). The first correlations were better described with exponential fitting. MDS-UPDRS-III in ‘OFF’ state correlated negatively (p < 0.04) with BPND in the sensorimotor striatum (r s = − .47), and excluding tremor score also in the putamen (r s = − .45). Conclusion Results are in agreement with earlier findings in in vivo and post-mortem studies and validate [18F]FE-PE2I as a functional PD biomarker for PD severity. Trial registration: EudraCT 2011-0020050, Registered April 26 2011; EudraCT 2017-003327-29, Registered October 08 2017; EudraCT 2017-001585-19, Registered August 2 2017. https://eudract.ema.europa.eu/ .